Human detection sensors for car post-locking child detection system: article / Aliff Haqim Abdullah Yusuff - Abdullah Yusuff, Aliff Haqim (2014)
This project presents the use of human detection sensors for Post-Locking Child Presence Detection system. The aim of this project is to detect the presence of humans, especially children left unattended in cars. The system is made up of a sensing unit which consist of human detection sensors such as Passive Infrared (PIR) motion sensor, MEMS thermal sensor, and a built-in microphone, that runs on an Arduino Uno microcontroller. The MEMS thermal sensor works through temperature differentiation, PIR sensor detects motion and the built-in microphone detects voice through frequency selection. The human detection sensors are the initial triggers for the Post-Locking Child Presence Detection System. The system is effective in detecting presence of humans in the car which can lead to the reduction of child left unattended cars.